Overcoming the Interface Losses in Planar Heterojunction Perovskite‐Based Solar Cells. Issue 25 (4th May 2016) - Hou, Yi; Chen, Wei; Baran, Derya; Stubhan, Tobias; Luechinger, Norman A.; Hartmeier, Benjamin; Richter, Moses; Min, Jie; Chen, Shi; Quiroz, Cesar Omar Ramirez; Li, Ning; Zhang, Hong; et al.
Abstract : A scalable, hysteresis‐free and planar architecture perovskite solar cell is presented, employing a flame spray synthesized low‐temperature processed NiO (LT‐NiO) as hole‐transporting layer yielding efficiencies close to 18%. Importantly, it is found that LT‐NiO boosts the limits of open‐circuit voltages toward an impressive non‐radiative voltage loss of 0.226 V only, whereas PEDOT:PSS suffers from significant large non‐radiative recombination losses.